The metabolic health of young men conceived using intracytoplasmic sperm injection. Issue 12 (27th September 2022) - Catford, S R; Halliday, J; Lewis, S; O'Bryan, M K; Handelsman, D J; Hart, R J; McBain, J; Rombauts, L; Amor, D J; Saffery, R; McLachlan, R I
Abstract: STUDY QUESTION: Is the metabolic health of men conceived using ICSI different to that of IVF and spontaneously conceived (SC) men? SUMMARY ANSWER: ICSI-conceived men aged 18–24 years, compared with SC controls, showed differences in some metabolic parameters including higher resting diastolic blood pressure (BP) and homeostasis model assessment for insulin resistance (HOMA-IR) scores, although the metabolic parameters of ICSI- and IVF-conceived singleton men were more comparable. WHAT IS KNOWN ALREADY: Some studies suggest that IVF-conceived offspring may have poorer cardiovascular and metabolic profiles than SC children. Few studies have examined the metabolic health of ICSI-conceived offspring. STUDY DESIGN, SIZE, DURATION: This cohort study compared the metabolic health of ICSI-conceived men to IVF-conceived and SC controls who were derived from prior cohorts. Participants included 121 ICSI-conceived men (including 100 singletons), 74 IVF-conceived controls (all singletons) and 688 SC controls (including 662 singletons). PARTICIPANTS/MATERIALS, SETTING, METHODS: Resting systolic and diastolic BP (measured using an automated sphygmomanometer), height, weight, BMI, body surface area and fasting serum metabolic markers including fasting insulin, glucose, total cholesterol, high-density lipoprotein cholesterol (HDLC), low-density lipoprotein cholesterol, triglycerides, highly sensitive C-reactive protein (hsCRP) and HOMA-IR were compared between groups. Data were analysed using multivariable linear regression adjusted for various covariates including age and education level. MAIN RESULTS AND THE ROLE OF CHANCE: After adjusting for covariates, compared to 688 SC controls, 121 ICSI-conceived men had higher diastolic BP ( β 4.9, 95% CI 1.1–8.7), lower fasting glucose ( β −0.7, 95% CI −0.9 to −0.5), higher fasting insulin (ratio 2.2, 95% CI 1.6–3.0), higher HOMA-IR (ratio 1.9, 95% CI 1.4–2.6), higher HDLC ( β 0.2, 95% CI 0.07–0.3) and lower hsCRP (ratio 0.4, 95% CI 0.2–0.7) levels. Compared to 74 IVF-conceived singletons, only glucose differed in the ICSI-conceived singleton men ( β −0.4, 95% CI −0.7 to −0.1). No differences were seen in the paternal infertility subgroups. LIMITATIONS, REASONS FOR CAUTION: The recruitment rate of ICSI-conceived men in this study was low and potential for recruitment bias exists. The ICSI-conceived men, the IVF-conceived men and SC controls were from different cohorts with different birth years and different geographical locations. Assessment of study groups and controls was not contemporaneous, and the measurements differed for some outcomes (BP, insulin, glucose, lipids and hsCRP). WIDER IMPLICATIONS OF THE FINDINGS: These observations require confirmation in a larger study with a focus on potential mechanisms. Further efforts to identify whether health differences are due to parental characteristics and/or factors related to the ICSI procedure are also necessary. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by an Australian National Health and Medical Research Council Partnership Grant (NHMRC APP1140706) and was partially funded by the Monash IVF Research and Education Foundation. S.R.C. was supported through an Australian Government Research Training Program Scholarship. R.J.H. is supported by an NHMRC project grant (634457), and J.H. and R.I.M. have been supported by the NHMRC as Senior and Principal Research Fellows respectively (J.H. fellowship number: 1021252; R.I.M. fellowship number: 1022327). L.R. is a minority shareholder and the Group Medical Director for Monash IVF Group, and reports personal fees from Monash IVF Group and Ferring Australia, honoraria from Ferring Australia and travel fees from Merck Serono and MSD and Guerbet; R.J.H. is the Medical Director of Fertility Specialists of Western Australia and has equity in Western IVF; R.I.M. is a consultant for and shareholder of Monash IVF Group and S.R.C. reports personal fees from Besins Healthcare and nonfinancial support from Merck outside of the submitted work. The remaining authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: N/A.